2011
DOI: 10.1016/j.funbio.2010.12.014
|View full text |Cite
|
Sign up to set email alerts
|

A genetically homogenous population of Fusarium circinatum causes pitch canker of Pinus radiata in the Basque Country, Spain

Abstract: Pitch canker, caused by Fusarium circinatum, is a destructive disease of Pinus species and has recently been shown to represent a substantial threat to natural and commercial forests in northern Spain. The genetic diversity of F. circinatum in the Basque Country of Spain was assessed by characterising 96 isolates based on vegetative compatibility groups (VCGs), mating type assays, polymorphic DNA-markers and amplified fragment length polymorphism (AFLP) analyses. For this purpose, F. circinatum isolates were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 46 publications
2
59
0
2
Order By: Relevance
“…An analysis of more extensive collections of isolates and the application of markers such as microsatellites or vegetative compatibility groups will provide a much clearer view of the population biology and origin of F. circinatum in Colombia. Such studies have shown, for example, that F. circinatum in California was introduced from the southeastern United States (Wikler and Gordon 2000) and that pitch canker in northern Spain is probably due to one or a few introductions (Iturritxa et al 2011). A detailed understanding of the population biology of F. circinatum in Colombia should, therefore, reveal whether the pathogen originated from contaminated seed that was imported from Mexico or Central America, as have been shown for the pathogen in South Africa (Britz et al 2001;Wikler and Gordon 2000), or from some other source.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of more extensive collections of isolates and the application of markers such as microsatellites or vegetative compatibility groups will provide a much clearer view of the population biology and origin of F. circinatum in Colombia. Such studies have shown, for example, that F. circinatum in California was introduced from the southeastern United States (Wikler and Gordon 2000) and that pitch canker in northern Spain is probably due to one or a few introductions (Iturritxa et al 2011). A detailed understanding of the population biology of F. circinatum in Colombia should, therefore, reveal whether the pathogen originated from contaminated seed that was imported from Mexico or Central America, as have been shown for the pathogen in South Africa (Britz et al 2001;Wikler and Gordon 2000), or from some other source.…”
Section: Discussionmentioning
confidence: 99%
“…The disease also occurs on native Pinus species in Haiti (Hepting and Roth 1953), Japan (Kobayashi and Muramoto 1989), Korea (Woo et al 2010) and Italy (Carlucci et al 2007). In Spain, South Africa, and Korea pitch canker occurs in planted stands of important non-native forestry species (Coutinho et al 2007;Iturritxa et al 2011;Landeras et al 2005;Lee et al 2000;Woo et al 2010). In Spain, South Africa, Chile, Portugal and Uruguay, F. circinatum further also limits seedling production in commercial forestry nurseries (Alonso and Bettucci 2009;Bragança et al 2009;Landeras et al 2005;Wingfield et al 2002aWingfield et al , 2002b.…”
Section: Fusarium Circinatum Has a Global Distribution And Is Capablementioning
confidence: 99%
“…This isolate was identified to be in vegetative compatibility group (VCG) A and Mating type 2 (Mat-2), the only mating type present in the Basque Country [25]. This isolate is stored on small pieces of sterile filter paper (Whatman no.1) at −20 °C.…”
Section: Seed Disinfestation and Inoculation With Fusarium Circinatummentioning
confidence: 99%
“…; Dolichopodidae) have been identified as carriers of PPCD fungus in the USA, as summarized by Brockerhoff et al [9]. In Spain, all identified carriers of F. circinatum belong to Curculionidae, including seven species of Scolytinae, one Molytinae and one Entiminae [10,11].…”
Section: Introductionmentioning
confidence: 99%